Gejala serangan dan tingkat serangan Sparganobasis subcruciata Marshall sebagai hama baru pada kelapa sawit di Indonesia bagian timur - Agus Eko Prasetyo; Tjut Ahmad Perdana Rozziansha; Muhayat Muhayat; Roch Desmier de Chenon (Jurnal Entomologi Indonesia, 2019)
Sparganobasis subcruciata Marshall is a species of weevil occurring in Papua and eastern parts of Indonesia, which had been begun found to causes damage to oil palm in the Boven Digoel district. The research was carried out to investigate the symptoms of S. subcruciata attack and it’s damage level in one of oil palm plantation in Boven Digoel. The result shows that larvae of this weevil bore into the stem, particularly the lower part, giving rise to symptoms which are similar to symptoms of Ganoderma disease, specifically the occurrence of more than three leaves in the spear failing to open, hanging down and drying out and the ultimate death of the palm. The weevil has been detected in Boven Digoel, Papua, where significant numbers of oil palms appeared to be dead or dying in each of the plantation visited by us. We consider that this weevil constitutes a major threat to oil palm plantations in Papua and that it may in the future, if it is not already the case, be a threat to plantations in Eastern Indonesia. Early detection of the presence of the weevil is difficult and requires research, as do methods of control, which we suggest should focus on the development and use of pheromones.